Export and Change Yourself: Key Challenges for Fast-growing Technology Companies in Russia - D. S. Medovnikov; S. D. Rozmirovich (Мир новой экономики, 2019)
The article presents the results of a survey of the Russian fast-growing innovative companies participating in the national rating “Techuspekh”. As a part of the study, we 81 surveyed companies and interviewed the company’s ten executives. The aim of the researchers was an analysis of the development of export companies and solving their organisational and management problems. More than half of the companies consider the domestic market as a priority. However, despite this, three-quarters of firms operate in foreign markets. The share of exports in revenue is still small and averages 10 per cent. It seems that companies are more likely to probe foreign markets. Financial terms of supply, organisation of after-sales service, advertising and work with the brand remain the weak side of exporting companies. The main directions of organisational and managerial changes in these companies over the past three years were: scaling of production capacity, digitalisation of business, development of HR-system and development of work with consumers. Among the main organisational problems to be solved in the future, the companies mentioned the weak development of sales in foreign markets, the problems of stimulating and motivating staff, and the lack of efficiency of existing business processes. At the same time, many of the surveyed managers do not pay enough attention to the systematic work on the analysis of changes in the organisational and managerial environment of the company and the planning of measures to improve it.